2021
DOI: 10.47815/apsr.2021.10026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intercropping on growth and yield of tomato (Solanum lycopersicum L.)

Abstract: The investigation was carried out to “Study the effect of intercropping on growth and yield of tomato (Solanum lycopersicum L.)” at a farmer’s field at Sorakalnatham, Natrampalli taluk, Tirupattur district, (Tamil Nadu) during January - May 2019. The experiment was laid out in randomized block design with ten treatments replicated thrice. The treatments comprised of three intercrops viz., radish, small onion and vegetable cowpea, and three levels of recommended dose of fertilizers (RDF) viz., 100, 125 and 150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…Similar findings were obtained by Islam et al, [5]. Similarly, Soniya et al, [6] observed that increasing the levels of recommended doses of fertilizers helps in increasing the growth and yield of radish in tomato and radish intercropping combination.…”
Section: Yield and Quality Characters Of Radishsupporting
confidence: 84%
“…Similar findings were obtained by Islam et al, [5]. Similarly, Soniya et al, [6] observed that increasing the levels of recommended doses of fertilizers helps in increasing the growth and yield of radish in tomato and radish intercropping combination.…”
Section: Yield and Quality Characters Of Radishsupporting
confidence: 84%
“…Similar findings were obtained by Ahamed, 2019). Similarly, Soniya et al [4] observed that increasing the levels of recommended doses of fertilizers helps in increasing the growth and yield of radish intercropping combination.…”
Section: Yield and Quality Characters Of Radishmentioning
confidence: 94%
“…Panda et al [56] recorded the highest values of growth parameters, viz. plant height (118.4 and 131.7 cm), stem girth (2.56 and 3.25 cm) and number of leaves plant -1 (80.5 and 104.2) at 50 and 75 DAT, respectively, in tomato cv.…”
Section: Effect On Growth Parametersmentioning
confidence: 97%
“…The significant enhancement in yield attributes and yield may be attributed to the combined effect of increased supply of plant nutrient ions and biofertilisers present in Panchagavya, and increased allocation of food materials to the developing fruits. Panda et al [56] recorded the maximum yield attributes, viz. fruit length (5.60 cm), number of fruits plant -1 (46.1), fruit diameter (4.41 cm) and fruit yield plant -1 (2.81 kg) in tomato cv.…”
Section: Effect On Yield Parametersmentioning
confidence: 99%